Essential Oil Compositions and Bioactivities of Thymus revolutus and Cyclotrichium origanifolium - Gokturk, R. Suleyman; Sagdic, Osman; Ozkan, Gulcan; Unal, Orhan; Aksoy, Ahmet; Albayrak, Sevil; Arici, Muhammet; Durak, M. Zeki (TAYLOR & FRANCIS LTD, 2013)
Thymus revolutus Celak (Lamiaceae) is an endemic species in Turkey. Cyclotrichium origanifolium (Labill.) Manden & Scheng (Lamiaceae) has been widely used as a flavoring agent in soups and salads, and herbal tea in Turkey. The essential oil (EO) components, antioxidant and antimicrobial activities of the extracts and EOs of T. revolutus and C. origanifolium were examined. The EO compositions were analyzed by GC-MS. Total phenolic contents, flavanols, flavonols and antioxidant activities of the extracts were determined by spectrophotometer. Antimicrobial activity was investigated against 15 microorganisms by agar diffusion method. Carvacrol, thymol, p-cimene and borneol were predominantly found in T. revolutus EO. The C. origanifolium EO contained bicyclo[3.1.1]hepten-3-one, 2,6,6-trimethyl-,(1.alpha, 2.beta, 5.alpha), pulegone and 2-cylohexen-1-ol, 1-methyl-4-(1-methylethyl),-cis as main constituents. The levels of total phenolic contents, flavanols, and flavonols of T. revolutus and C. origanifolium extracts were 38.68 +/- 2.5 and 78.57 +/- 0.6 mg gallic acid equivalent/g; 2250.06 +/- 328.0 and 610.84 +/- 13.3 mg catechin equivalent/100 g; and 1287.35 +/- 91.1 and 2712.36 +/- 20.9 mg rutin equivalent/100 g, respectively. Antioxidant activities of T. revolutus and C. origanifolium were 48.91 +/- 0.2 % and 74.86 +/- 0.3 % at 0.1 mg/mL concentration, respectively in the DPPH assay. C. origanifolium EO sat 2 % and 1 % concentrations showed antibacterial activity against tested Gram (+) bacteria but not Mycobacterium smegmatis. Both of the EOs had no inhibitory effects at 0.2 and 0.5 % concentrationson on the 15 tested microorganisms. Gram (+) bacteria found to be more sensitive to the EOs and extracts than Gram (-) bacteria in this study. The EOs and the extracts of T. revolutus and C. origanifolium could be used as natural products in many areas such as food, pharmaceutical, alternative medicine and natural therapy.
Keywords: Thymus revolutus; Cyclotrichium origanifolium; essential oil composition; antimicrobial activity; antioxidant activity; ANTIOXIDANT ACTIVITIES; CHEMICAL-COMPOSITION; METHANOL EXTRACTS; VULGARIS L.; ANTIBACTERIAL; MANDEN.; SCHENG; NIVEUM; LEAVES; TURKEY; Plant Sciences